Residents perspectives on tourism impacts of Portuguese World Heritage historic centers: Angra do Heroísmo and Évora - Vareiro,Laurentina (2015)
The aim of this study is twofold. First, the study analyzes local community perspectives of the importance of the World Heritage Site (WHS) classification of the historic centers of Angra do Heroísmo and Évora. Second, the study analyzes local residents perceived tourism impacts on the municipalities of Angra do Heroísmo and Évora. The methodology comprises quantitative research based on a self-administered survey applied to convenience samples of local residents of the two Portuguese municipalities in 2014. The main results reveal that local residents have a strongly positive perception of the WHS designation in both municipalities. With regard to the perceived tourism impacts, residents from Angra do Heroísmo have a stronger agreement about the impacts of tourism on their city than the residents of Évora, except for the negative social and cultural impacts. The comparison of the mean scores of these impacts across residents that live near and far from the historic centers reveals that the most valued and least valued impacts in the three categories of impacts (economic, social and cultural, and environmental) are common to all groups of residents. Nevertheless, residents living in or near the historic center of Angra do Heroísmo have higher means in the majority of tourism impacts (in all categories), with only one negative impact to concern the majority of respondents. Among the residents from Évora, residents living in or near the historic center have higher means in the majority of economic impacts but lower means in almost all social and cultural impacts. With regard to the environmental impacts, residents living in or near the historic center have higher means scores in the positive impacts and lower means scores in the negative environmental impacts.